Analysis of trapped mosquito excreta as a noninvasive method to reveal biodiversity and arbovirus circulation. (18th October 2022) - L'Ambert, Grégory; Gendrot, Mathieu; Briolant, Sébastien; Nguyen, Agnès; Pages, Sylvain; Bosio, Laurent; Palomo, Vincent; Gomez, Nicolas; Benoit, Nicolas; Savini, Hélène; Pradines, Bruno; Durand, Guillaume André; et al.
Abstract: Emerging and endemic mosquito‐borne viruses can be difficult to detect and monitor because they often cause asymptomatic infections in human or vertebrate animals or cause nonspecific febrile illness with a short recovery waiting period. Some of these pathogens circulate into complex cryptic cycles involving several animal species as reservoir or amplifying hosts. Detection of cases in vertebrate hosts can be complemented by entomological surveillance, but this method is not adapted to low infection rates in mosquito populations that typically occur in low or nonendemic areas. We identified West Nile virus circulation in Camargue, a wetland area in South of France, using a cost‐effective xenomonitoring method based on the molecular detection of virus in excreta from trapped mosquitoes. We also succeeded at identifying the mosquito species community on several sampling sites, together with the vertebrate hosts on which they fed prior to being captured using amplicon‐based metabarcoding on mosquito excreta without processing any mosquitoes. Mosquito excreta‐based virus surveillance can complement standard surveillance methods because it is cost‐effective and does not require personnel with a strong background in entomology. This strategy can also be used to noninvasively explore the ecological network underlying arbovirus circulation.